Analysis of marine controlled source electromagnetic data for the assessment of gas hydrates in the Danube deep-sea fan, Black Sea. (December 2020) - Schwalenberg, Katrin; Gehrmann, Romina A.S.; Bialas, Jörg; Rippe, Dennis
Abstract: Marine controlled source electromagnetic (CSEM) data have been analyzed as part of a larger interdisciplinary field study to reveal the distribution and concentration of gas hydrates and free gas in two working areas (WAs) in the offshore Danube fan in the western Black Sea. The areas are located in the Bulgarian sector in about 1500 m water depth (WA1) and in the Romanian sector in about 650 m water depth (WA2). Both areas are characterized by channel levee systems and wide spread occurrences of multiple bottom simulating reflections (BSRs) suggesting the presence of gas hydrates. Electrical resistivity models have been derived from two-dimensional (2D) inversions of inline CSEM data using a seafloor-towed electric dipole-dipole system. Comparing the resistivity models with coincident reflection seismic profiles reveals insight in the sediment stratigraphy of the gas hydrate stability zone (GHSZ). Gas hydrate and free gas saturation estimates have been derived with a stochastic approach of Archie's relationship considering uncertainties in the input parameters available from drilling with the MeBo-200 seafloor rig in WA2. The resistivity models generally reflect the transition of marine to lacustrine conditions expressed by a sharp decay of pore water salinities in the top 30–40 m below seafloor caused by freshwater phases of the Black Sea due to sea level low stands in the past. In WA1, we derived saturation estimates of 10–20% within a 100 m thick layer at around 50 m depth below the channel which compares well with estimates from seismic P-wave velocities. The layer extends below the western levee with even higher saturations of 20–30%, but high gas hydrate saturations are unlikely within the fine grained, clayey sediment section, and the high resistivities may reflect different lithologies of lower permeability and porosity. The resistive layer terminates below the eastern levee where increasing resistivities at depth towards a stack of multiple BSRs indicate gas hydrate and free gas concentrations in the order of 10% to locally 30%. WA2 is characterized by a major slope failure at the landward edge of the gas hydrate stability field next to the channel. Gas hydrate saturation estimates within the slump area are close to zero within the GHSZ which is in agreement with coring results of the nearby MeBo drill sites. Elevated resistivities below the steeply upward bending BSR lead to saturation estimates less than 10% of free gas that may have accumulated. Highlights: First 2D CSEM study on Black Sea gas hydrates. Joint Interpretation of marine CSEM, seismic and drilling data. Stochastic determination of gas hydrate saturation estimates.